Angulasi Gigi Pasca Perawatan Ortodonti dengan Pencabutan dan Tanpa Pencabutan (Kajian Foto Rontgen Panoramik di Klinik Ortodonti FKG UI) - Safra Mauna; Maria Purbiati; Krisnawati Krisnawati (Journal of Dentistry Indonesia, 2012)
At the end of treatment with extraction, it is often found root paralleling problem on upper second insicive, lower premolar and adjacent teeth of extraction. This caused by failure of angulation correction on finishing stage. Objective : To describe whether any differences in angulation of teeth after treatment with extraction and without extraction of patients treated in Orthodontic Clinic, RSGM FKGUI. Material and methods : The angulation measurement is done by using Ursi methode on panoramic radigraphic. Result : Based on independent t test analysis, there were a significant differences (p<0.05) between tooth angulation after orthodontic treatment with extraction and without extraction on upper right second premolar and upper left canine, also on lower right canine and lower left second premolar, whereas there are no difference. Conclusion : It appeared that, tooth angulation after orthodontic treatment has a significant differences between extraction case and non extraction case (adjacent teeth of extraction). Panoramic radiograph required before finishing stage to evaluate tooth angulation and root parallelism for increase stability after orthodontic treatment. DOI: 10.14693/jdi.v16i1.16